The Right to Health and the Health Effects of Denials - Sonia R. Bhalotra; Manuel Fernandez Sierra (Institute of Labor Economics (IZA), 2021)
We estimate the health costs of supply-side barriers to accessing medical care. The setting is Colombia, where citizens have a constitutional right to health care, but insurance companies that manage delivery impose restrictions on access. We use administrative data on judicial claims for health as a proxy for unmet demand. We validate this using the register recording all health service utilization, estimating that a one standard deviation increase in judicial claims is associated with pervasive decreases in utilization rates of between 0.25 and 0.71 standard deviations, including in medical consultations, procedures, hospitalizations and emergency care. These restrictions on access manifest in population health outcomes. We estimate that a one standard deviation increase in judicial claims increases the all-cause mortality rate by between 0.10 and 0.23 standard deviations. Increases in mortality are pervasive across causes, with the largest increase in deaths from certain cancers. They are also pervasive across the age and sex distribution but larger among individuals over the age of fifty and (weakly) among women and the low-income population.
Keywords: I11; I13; I18; K4; 330; health care; health insurance; mortality; right-to-health; litigation; universal-health-coverage; Colombia